1992
DOI: 10.1088/0031-9155/37/3/021
|View full text |Cite
|
Sign up to set email alerts
|

Limited-angle 3D reconstruction of PET images for dose localization in light ion tumour therapy

Abstract: In vivo dose localization in light ion tumour therapy can be performed by measuring the range distributions of beta+ active ions in tissue employing positron emission tomographic techniques. For this purpose a multiplicative iteration scheme for reconstructing three-dimensional images from shift-variant, limited-angle data is presented. In the iterative correction steps the algorithm uses the geometric means of quotients calculated from the three-dimensional Radon transforms of the backprojected measured and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The most innovative system for quality control at the GSI pilot project was the development and installation of an in-beam Positron Emission Tomography (PET) system to trace the carbon ion beam inside the patient [57] . Clinically, PET scanners are normally used to measure organ functions after the injection of specific metabolic tracer labeled with positron emitting isotopes.…”
Section: The Heavy Ion Therapy Project At Gsimentioning
confidence: 99%
See 1 more Smart Citation
“…The most innovative system for quality control at the GSI pilot project was the development and installation of an in-beam Positron Emission Tomography (PET) system to trace the carbon ion beam inside the patient [57] . Clinically, PET scanners are normally used to measure organ functions after the injection of specific metabolic tracer labeled with positron emitting isotopes.…”
Section: The Heavy Ion Therapy Project At Gsimentioning
confidence: 99%
“…For the measurement, a PET camera was shifted over the treated area of the patient and the location of the positron decay inside the patient was recorded without extra exposure to the patient [59] .
Figure 8 The dose distribution of a stopping carbon beam (dashed line) is compared to the β+ activity (red) induced by the carbon ions (reproduced from [57] , [60] ).
…”
Section: The Heavy Ion Therapy Project At Gsimentioning
confidence: 99%
“…The interactions may serve advantages for the therapy verification with the similar mechanisms as positron emission tomography (PET) imaging. Verification of dose delivery to the tumor is possible by taking advantage of the property of positrons in producing 511 keV annihilation gamma photons [22,23]. These isotopes travel almost the same velocity as the main beam and stop in almost the same place and they emit gamma rays to be detected in a conventional PET scanner.…”
Section: Interactions Of Particles With Mattermentioning
confidence: 99%
“…Measurement of the 16 O and 12 C activities was started 5 min after the irradiation. Each of the H 2 O and CH 2 targets was positioned so the X-ray beam direction was parallel to the transverse imaging plane, thereby allowing full detection of all the annihilation gamma rays generated from the positrons (Fig.…”
Section: High-energy Photon Beam To H 2 O and Ch 2 Targetsmentioning
confidence: 99%
“…Simulation studies and experimental results were reported for charged ion treatment. [12][13][14][15][16] For high-energy photon treatment, the use of PET-CT at 50 MV was proposed; and experimental results [17][18][19][20] and Monte Carlo calculation results were also reported for in-beam PET imaging. 21 The purpose of this article is to show that 15 O and 11 C positron emitter nuclei can be detected using a commercial PET-CT in the photonuclear reaction with X-ray energy as low as 21 MV.…”
Section: Introductionmentioning
confidence: 99%